Democratic Republic of the Congo : Selected Issues. (IMF Staff Country Reports; Country Report, 2019)
This Selected Issues paper focuses on macro-critical issues related to governance and corruption in Democratic Republic of the Congo (DRC). Third-party indicators suggest that governance has been poor and corruption widespread in the country. Conducting an audit of the civil service and improving the transparency of its remuneration system, simplifying tax payment processes, and merging the activities of the numerous revenue agencies would boost public efficiency and improve the business environment. Contract enforcement and protection of property rights could be enhanced by insulating the courts from external influence. Limited information on the budget annexes and special accounts and little or no oversight by the central government, Parliament, and civil society, create scope for corruption. The multiplicity of special taxes and fees, some accruing to special accounts outside the Treasury, generate opportunities for corruption and informalization of economic activity. Despite some progress in strengthening public financial management, budget execution remains deficient. The government has formalized the four stages of the expenditure chain and introduced budget commitment plans to align expenditures with revenues.